Model for Quality of Life Evaluation of Countries European Union with using Rule-based Systems - Šanda, Martin; Křupka, Jiří (SciTePress - Science and Technology Publications, 2017)
This paper deals with the quality of life (QL) evaluation of countries European Union (EU) and progress of this evaluation in years 2007, 2011 and 2015. QL evaluation is based on official Eurostat methodology for QL evaluation - QL indicators for the EU, the data presented here come from several sources from within the European Statistical System (ESS). The set of indicators is organised along the areas: Material living conditions, Productive or main activity, Health, Education, Economic and physical safety, Governance and basic rights and Natural and living environment. QL is evaluated with using rule-based systems method: Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) - modification fuzzy TOPSIS fuzzy inference system (FIS) and Analytic hierarchy process (AHP). The aim of this paper is creating model for QL evaluation with using these methods, comparing results of these methods and their progression. Result of model is final recommendation to reach the grant allocation for the countries or regional development.
Model pro hodnocení kvality života zemí Evropské unie pomocí pravidlových systémů
Keywords: AHP; EU; Fuzzy Sets; Fuzzy Inference System; Quality of Life Evaluation; Rule-based Systems; TOPSIS; AHP; EU; fuzzy množiny; fuzzy inferenční systém; hodnocení kvality života; pravidlové systémy; TOPSIS